Driving SDGs with Talas Beneng: Green Products for a Sustainable Future - Putri, Nia Ariani; Cahyani, Ferina Ardhi (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2024)
Environmental issues, driven by the growing number of industries, including food production, are a pressing concern. This research focuses on introducing green product principles to producers of Talas Beneng chips, a traditional Banten snack, to address the environmental impact of their production processes. Despite the popularity of Talas Beneng-based products, improper waste management during production poses ecological risks. This study emphasizes the urgency of educating small-scale producers on sustainable practices to minimize environmental harm. The initiative involved structured stages: initial surveys, field visits, literature reviews, socialization, education, and evaluation. The program successfully enhanced participants’ understanding of green products, highlighting the importance of sustainable production to mitigate environmental damage. By aligning local food practices with sustainable development goals, this effort contributes to fostering environmentally conscious industries and promotes the adoption of green product principles at the grassroots level, bridging tradition and innovation for a sustainable future.